2021
DOI: 10.15282/ijleal.v11.5231
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kesilapan Sintaksis Bahasa Arab dalam Penulisan Karangan Pelajar Natif Bahasa Melayu

Abstract: Kajian ini membincangkan aspek penggunaan sintaksis nahu Arab yang terdapat di dalam sistem nahu bahasa Arab dan bentuk kesilapan penggunaannya di dalam penulisan pelajar bahasa Arab di Universiti Sains Islam Malaysia (USIM). Responden kajian terdiri daripada lepasan sekolah dan ma’ahad agama seluruh negara. Umum mengetahui bahawa bahasa Arab tidak asing kepada para pelajar ini yang terdiri daripada kalangan pelajar pengajian agama dan mereka telah lama mengikuti pembelajaran bahasa ini secara formal bermula d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 0 publications
4
6
0
2
Order By: Relevance
“…Their results showed that students find it more difficult to use past tense verb ‫الماضي(‬ ‫)الفعل‬ than the present tense verb ‫المضارع(‬ ‫)الفعل‬ that is by using the present tense verb ‫"يعملون"‬ (they do) in construction of the sentence "they did". Their findings are in line with the study conducted by Ismail et al (2021) who also found it is more difficult for students to use past tense than present tense, for example in the sentence " ‫من‬ ‫أنتهي‬ ‫الماضية‬ ‫سنة‬ ‫في‬ ‫الثانوية‬ ‫"المدرسة‬ (I finish from high school last year) by using present tense ‫"أنتهي"‬ (I finish) which should be the past tense verb " ‫ْت‬ ‫ي‬ َ ‫َه‬ ‫ْت‬ ‫"ان‬ (I finished). Sopian (2019) also found that students find it difficult to use verbs in learning Arabic grammar.…”
Section: A a Study Of Arabic Grammar Mastery Among Students In Malaysiasupporting
confidence: 89%
See 2 more Smart Citations
“…Their results showed that students find it more difficult to use past tense verb ‫الماضي(‬ ‫)الفعل‬ than the present tense verb ‫المضارع(‬ ‫)الفعل‬ that is by using the present tense verb ‫"يعملون"‬ (they do) in construction of the sentence "they did". Their findings are in line with the study conducted by Ismail et al (2021) who also found it is more difficult for students to use past tense than present tense, for example in the sentence " ‫من‬ ‫أنتهي‬ ‫الماضية‬ ‫سنة‬ ‫في‬ ‫الثانوية‬ ‫"المدرسة‬ (I finish from high school last year) by using present tense ‫"أنتهي"‬ (I finish) which should be the past tense verb " ‫ْت‬ ‫ي‬ َ ‫َه‬ ‫ْت‬ ‫"ان‬ (I finished). Sopian (2019) also found that students find it difficult to use verbs in learning Arabic grammar.…”
Section: A a Study Of Arabic Grammar Mastery Among Students In Malaysiasupporting
confidence: 89%
“…The students form the present tense ‫"تكتب"‬ (you write), instead of ‫ب"‬ ‫ت‬ ْ ‫"أك‬ (I write) because the doer refers to the first person (me). The findings of Sopian's (2019) study are different from the study of Sokri and Ismail (2017) and the study of Ismail et al (2021).…”
Section: A a Study Of Arabic Grammar Mastery Among Students In Malaysiamentioning
confidence: 63%
See 1 more Smart Citation
“…Bahasa Arab disebut pula bahasa dogma(agama) yang digunakan umat Islam sejajar dengan bahasa yang digunakan dalam wahyu al-Qur'an dan hadis baginda Rasulullah shallallahu 'alaihi wasallam, yang lahir di kalangan warga penutur bahasa tersebut (Ismail, Mohamed, Razak, Hj Ibrahim, & Isa, 2021). Bahasa Arab merupakan bahasa yang kebanyakan diajarkan pada forum-forum Islam, khususnya pesantren (Nurhidayah, 2021).…”
Section: Pendahuluanunclassified
“…Menurut al-Imrithi pada (Sulaikho & Mathoriyah, 2020) dalam struktur kebahasaan bahasa arab, waktu istilah tersusun sebagai kalimat maka masih ada perubahan gramatikal berupa ditambahkannya alfabet baru dalam akhir istilah waktu merujuk dalam subjek perempuan, subjek ganda, atau subjek majemuk. Sistem sintaksis menaruh fokus krusial pada aspek keseragaman perkataan (words agreement), berdasarkan sudut keserasian tawabi`, infleksi atau baris akhir perkataan (case of ending) yg mensugesti makna ayat & menaruh kesan akbar pada kedudukan perkataan pada urutan perkataan (word order) & konteks makna (Ismail, Mohamed, Razak, Hj Ibrahim, & Isa, 2021). Dalam struktur sintaksis terdapat 3 macam pembahasan; fungsi sintaksis, kategori sintaksis, & kiprah sintaksis.…”
Section: Pendahuluanunclassified